Primary Sjögren’s syndrome presenting with hypokalemic periodic paralysis: A case series - Margi Dipakkumar Patel; Naman Ashokbhai Popat; Chiranjeev Dilipkumar Mehta; Dharmendra J Vatsaraj (Asian Journal of Medical Sciences, 2025)
Tubulointerstitial nephritis (TIN) is the primary renal involvement associated with primary Sjögren’s syndrome (pSS). We present a series of female patients with hypokalemic paralysis due to distal renal tubular acidosis. The patients received symptomatic treatment, including potassium supplementation, with favorable responses. The evidence suggests an underlying inflammatory mechanism that can lead to serious complications such as hypokalemic paralysis. Based on our findings, a combination of potassium supplementation and corticosteroid therapy is suggested for managing pSS-associated TIN.